The Path That Changes Everything. Reportages About Refugees Based on Kenneth Burke’s Dramatism Theory - Sarna, Paweł; Tyc, Ewelina (Porównania, 2025)
Forced migration has become an important topic in nonfiction in recent years. The authors of the article analyze two contemporary reportage books – Nawet jeśli umrę w drodze (Even if I Die on the Way) by Monika Białkowska and The Naked Don’t Fear the Water. An Underground Journey with Afghan Refugees by Matthieu Aikins – based on Kenneth Burke’s concept of dramatism. Both reportages present the fate of refugees who set out on a risky and unknown journey in search of safety. Their authors draw attention to a broader social problem – a reaction to the arrival of migrants that may undermine the fundamental principles of humanism and solidarity. This analysis shows how the scene, as the dominant element of the pentad, determines the other elements in reportages – act, agent, agency and purpose – and what are the relations between them. The use of Burke’s pentad allows us to show the tragic nature of a refugee’s plight, forced by circumstances to make desperate decisions. They become not only victims of a series of unfavourable circumstances, but also active subjects striving to survive and enter dialogue.